Persepsi Siswa terhadap Keterampilan Mengajar Mahasiswa PLK UNP Program Studi Pendidikan Teknik Mesin di SMK Negeri 5 Padang (Jurnal Arjuna : Publikasi Ilmu Pendidikan, Bahasa dan Matematika, 2025)
Education plays an important role in improving the quality of human resources, where teachers serve as the key to the success of the teaching and learning process. Prospective teachers need to possess adequate knowledge and skills to carry out teaching responsibilities effectively. The Teaching Practice Program (PLK) - Teaching Assistance is a course designed to help students of the education program at Universitas Negeri Padang develop teaching skills before entering the professional education field. However, based on preliminary observations at SMK Negeri 5 Padang, it was found that PLK-Teaching Assistance students still lacked certain teaching skills, such as mastery of subject matter, use of media and teaching methods, and classroom management. This study aims to determine students' perceptions of the teaching skills of PLK-Teaching Assistance students at SMK Negeri 5 Padang. The results are intended as feedback and improvement to enhance the teaching skills of these students. The research used a quantitative approach. The population consisted of Grade X and XI students of the Mechanical Engineering program, with a total sample of 126 students. The results showed that students' perception of the teaching skills of PLK-Teaching Assistance students in the Mechanical Engineering Education program at SMK Negeri 5 Padang was categorized as good, with a percentage of 67%. This included: 1) questioning skills (56%), 2) reinforcement skills (56%), 3) explanation skills (56%), 4) teaching variation skills (51%), 5) opening and closing learning skills (55%), 6) small group and individual teaching skills (56%)—all categorized as good; and 7) classroom management skills (41%), and 8) small group discussion guidance skills (42%)—both categorized as less satisfactory. Therefore, overall, students' perception of the teaching skills of Universitas Negeri Padang's PLK-Teaching Assistance students in the Mechanical Engineering Education program at SMK Negeri 5 Padang was considered good.